2021
DOI: 10.1109/access.2021.3109013
|View full text |Cite
|
Sign up to set email alerts
|

Feature Selection for Interval-Valued Data Based on D-S Evidence Theory

Abstract: Feature selection is one basic and critical technology for data mining, especially in current "big data era". Rough set theory (RST) is sensitive to noise in feature selection due to the strict condition of equivalence relation. However, D-S evidence theory is flexible to measure uncertainty of information. This paper introduces robust feature evaluation metrics "belief function" and "plausibility function" into feature selection algorithm to avoid the defect that classification effect is affected by noise. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 46 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, several theoretical problems related to this approach remain open. These include finding theoretical conditions for equivalence between the two reduct definitions, the study of rule induction algorithms, as well as studying the properties of these definitions of reducts in the other generalized relation-based models that have been more recently considered in the literature [17,36,68,87,88,91].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several theoretical problems related to this approach remain open. These include finding theoretical conditions for equivalence between the two reduct definitions, the study of rule induction algorithms, as well as studying the properties of these definitions of reducts in the other generalized relation-based models that have been more recently considered in the literature [17,36,68,87,88,91].…”
Section: Discussionmentioning
confidence: 99%
“…First, the same authors [110] considered the application of belief and plausibility reducts to random information systems, showing that Theorems 4.3 and 4.4 hold also in this setting. Furthermore, the extension to the case of continuous and interval-valued data has been widely studied [17,68,88], and it has been shown that the equivalence between belief and classical reducts holds also in these settings.…”
Section: Uncertainty In the Conditions: Belief Reductsmentioning
confidence: 99%